Chapter 8 - The state-of-the-art and challenges in the field of organic and inorganic biocompatible coatings for implants; Advances in 3D and 4D Printing of Medical Robots and Devices - Dinu Mihaela M.; Surmeneva M. A. Maria Alexandrovna; Kozadayeva M. Maria; Vitelaru Catalin C.; Abdulla S. Sukhananazerin; Morris Michael M. A.; Surmenev R. A. Roman Anatolievich; Padmanabhan S. C. Sibu; Vladesku A. Alina (2025, 2025)
In recent years, clinical practice has witnessed an extensive expansion and technological advancements, especially in areas surrounding biomedical engineering, focusing on enhancing the performance and biocompatibility of medical implants with various applications (orthopedic fixation devices, dental implants, maxillofacial reconstruction, spinal implants, etc.). The continuous research in this field aims to further enhance the properties of these biomaterials, exploring new options, surface modifications, and fabrication methods to optimize their performance and efficacy. In this context, continuous requirements in the field have led to the development of various coating techniques, such as physical vapor deposition (PVD), electrochemical deposition, magnetron sputtering, pulsed laser deposition (PLD), and sol–gel, each offering unique advantages in terms of coating uniformity, thickness control, and adherence to the implant surface. Inorganic biocompatible coatings for implants serve as an interface between the implant material and the biological environment, aiming to improve biointegration, durability, and functionality while minimizing adverse reactions within the body. The primary objective of these coatings is to address challenges such as corrosion, wear, and immune response, by providing a protective layer that favorably interacts with the surrounding biological tissues. The choice of coating material and technique is tailored to the specific application and implant type, considering site-specific biological interactions. For instance, titanium-based implants are often coated with hydroxyapatite (HA) to promote better bone integration, while bioceramic coatings improve the biocompatibility. Various studied inorganic coatings include bioinert metal oxide coatings (TiO2, Al2O3, ZrO2); calcium phosphate (CaP) coatings such as HA or tricalcium phosphate (TCP), which are the major mineral component of bone tissue; bioactive metallic glasses (ZrCuCa, ZrCuMg, ZrCuMo, ZrCuSi, ZrCuSr, etc.); nitrides (TiN, ZrN, CrN, NbN, TiAlN, TiSiN, ZrSiN, ZrTiN, ZrNbN, ZrTiSiN, etc.), oxynitrides (TiON, ZrON, CrON, TiSiON, etc.), carbides (TiC, TiSiC, TiZrC, TiNbC, TiSiZrC, etc.), carbonitrides (TiCN, TiCrSiCN, TiAlSiCN, TiSiCN, ZrCN, TiNbCN, TiZrCN, TiAlCN, TiAlZrCN, TiNbZrCN, TiZrSiCN, etc.), or carbon-based coatings such as diamond-like carbon (DLC). Overall, these coatings offer exceptional mechanical properties, resistance to degradation, and biocompatibility, ensuring compatibility with the host tissues